1994
DOI: 10.1021/bi00180a041
|View full text |Cite
|
Sign up to set email alerts
|

Models and Molecular Orbital Semiempirical Calculations in the Study of the Spectroscopic Properties of Bovine Serum Amine Oxidase Quinone Cofactor

Abstract: The electronic properties of 2,4,5-trihydroxyphenylalanine quinone (TPQ), the cofactor of bovine serum amine oxidase [Janes, S. M., Mu, D., Wemmer, D., Smith, A. J., Kaur, S., Maltby, D., Burlingame, A. L., & Klinman, J. P. (1990) Science 248, 981-987], and some adducts with hydrazines were investigated by means of low-molecular-weight models and semiempirical molecular orbital calculation methods. The enzyme visible band was assigned to the first pi-->pi* transition of the cofactor in p-quinonic form, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 31 publications
(37 reference statements)
6
29
0
Order By: Relevance
“…In another set of model studies, Bossa and fellow researchers confirmed that copper is not within bonding distance of the oxidized cofactor (29). These authors performed a detailed analysis of spectroscopic data obtained for low-molecular-weight models of the TPQ cofactor, with the aid of semiempirical molecular orbital calculation methods, in an attempt to gain a deeper insight into the cofactor electronic and basic structural features (29,(78)(79)(80).…”
Section: Tpq-copper and Tpq-protein Interactionsmentioning
confidence: 77%
See 4 more Smart Citations
“…In another set of model studies, Bossa and fellow researchers confirmed that copper is not within bonding distance of the oxidized cofactor (29). These authors performed a detailed analysis of spectroscopic data obtained for low-molecular-weight models of the TPQ cofactor, with the aid of semiempirical molecular orbital calculation methods, in an attempt to gain a deeper insight into the cofactor electronic and basic structural features (29,(78)(79)(80).…”
Section: Tpq-copper and Tpq-protein Interactionsmentioning
confidence: 77%
“…In particular, the investigation of the electronic properties of some adducts of 1,4-dihydroxy-2,5-benzoquinone (26; Fig. 3) with bases and hydrazines revealed that all the electronic transitions examined, although highly sensitive to cofactor ionization and hydrogen bonding, could be accounted for without introducing perturbations due to copper, thus disfavoring the possibility of a direct copper-TPQ interaction (29). These studies and, more recently, the AM1 and PM3 semiempirical calculations performed on the adducts between 26 or 4 and 4-(N,Ndimethyl)aminopyridine (81), also provided clues about the TPQ-protein interactions through hydrogen bonding.…”
Section: Tpq-copper and Tpq-protein Interactionsmentioning
confidence: 98%
See 3 more Smart Citations